UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT DAN BIJI BUAH SEMANGKA (Citrullus lanatus) MENGGUNAKAN METODE DPPH (1,1 diphenyl-2- picryhidrazyl) - ALFILA ALFILA (PHARMACY UMI JOURNAL SYSTEM, 2023)
ALFILA. Antioxidant Activity Test of Ethanol Extract of Watermelon (Citrullus lanatus) Peel and Seeds Using the DPPH (1,1 diphenyl-2-picryhidrazyl) Method (Supervised by Andi Amaliah Dahlia and Mamat Pratama).Watermelon is a member of the Cucurbitaceae family which is a type of pumpkin. Empirically it can be used as a traditional medicine for body conditioning, urine laxative, gastric and intestinal lubricant and anti-inflammatory drug. The purpose of this study was to determine the antioxidant activity of the ethanol extract of watermelon rind and seeds and to determine the value of the antioxidant activity of the ethanol extract of watermelon rind and seeds using the DPPH (1,1 diphenyl-2-picryhidrazyl) method. Samples were extracted by maceration method using 96% ethanol solvent. Quantitative tests were carried out on each extract using the UV-Vis spectrophotometry method. The absorbance was measured at a maximum wavelength of 516 nm using quercetin as a reference solution. The percent yield value of watermelon rind is 16.087% and watermelon seeds is 10.215%. The results of the IC50 value of the quercetin comparator are strong antioxidants because they have an IC50 value <50, namely 15,899 µg/mL, while watermelon rind is a strong antioxidant because it has an IC50 value between 50-100 µg/mL, namely 50,003 µg/, and watermelon rind includes strong antioxidant because it has an IC50 value between 50-100 µg/mL, namely 79.321 µg/mL.